2021
DOI: 10.1101/2021.10.05.461434
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunogenicity of SARS-CoV-2 trimetric spike protein associated to Poly(I:C) plus Alum

Abstract: The SARS-CoV-2 pandemic has had a social and economic impact worldwide, and vaccination is an efficient strategy for diminishing those damages. New adjuvant formulations are required for the high vaccine demands, especially adjuvant formulations that induce a Th1 phenotype. Herein we assess a vaccination strategy using a combination of Alum and polyinosinic:polycytidylic acid (Poly(I:C)) adjuvants plus the SARS-CoV-2 spike protein in a prefusion trimeric conformation by an intradermal (ID) route. We found high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 64 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…Recently, we demonstrated that the immunization of trimetric spike protein of SARS-CoV-2 that was associated to Poly(I:C) plus Alum was able to induce high neutralizing titers against SARS-CoV-2 in vitro by neutralization assay [7] by the i.d. route.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we demonstrated that the immunization of trimetric spike protein of SARS-CoV-2 that was associated to Poly(I:C) plus Alum was able to induce high neutralizing titers against SARS-CoV-2 in vitro by neutralization assay [7] by the i.d. route.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, many vaccine candidates against SARS-CoV-2 using the intradermal route (i.d.) have shown promising results, either on laboratory tests on different animal models [5][6][7][8], or in development with clinical trials [9,10]. The i.d.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microtitre plates (Immulon 2 HB) were coated with a trimeric mammalian-culture secreted ectodomain of the Spike protein—Wuhan in the pre-fusion conformation (Alvim et al, 2021 ) at 4 μg/ml or the nucleocapsid—Wuhan protein produced as described by dos-Santos et al ( 2021 ) at 1 μg/ml in 100 mM sodium carbonate-bicarbonate buffer (pH 9.6) and incubated overnight at 4°C. Excess protein was removed by washing five times with PBS + 0.05% Tween-20 (PBST, Sigma), and unbound sites were blocked using 5% BSA in PBST.…”
Section: Methodsmentioning
confidence: 99%